The Relationship Between Sleep Quality and Learning Concentration in Medical Students at Prima Indonesia University Class of 2022 - Hilda Ayu Tania; Ana Fresia; Taufik Delfian (CV. Inara, 2025)
Sleep represents a fundamental physiological necessity critical for restoring brain and body functions, with adequate sleep quality substantially influencing cognitive capacity and academic performance. Medical students frequently experience poor sleep quality due to demanding academic curricula, resulting in diminished learning concentration and compromised academic outcomes. This research examined the association between sleep quality and learning concentration among medical students at Universitas Prima Indonesia, class of 2022. An analytical observational cross-sectional study was conducted involving 67 medical students selected through simple random sampling. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while learning concentration was evaluated through structured observation sheets. Bivariate analysis employed chi-square statistical testing with a significance threshold established at p less than 0.05. Results demonstrated that 56.7% of participants experienced poor sleep quality, while 61.2% displayed low learning concentration. Chi-square analysis revealed a statistically significant association between sleep quality and learning concentration (p = 0.001), with an odds ratio of 11.652, indicating that students with good sleep quality possessed approximately 11.652 times greater likelihood of achieving high learning concentration. The strong association between these variables suggests that improving sleep quality represents a potentially effective intervention for enhancing concentration and academic performance in medical education. This research provides empirical evidence supporting the critical importance of sleep optimization within medical education institutions and justifies institutional investment in student wellness programs targeting sleep quality improvement and concentration enhancement.